New lipase producing β-proteobacteria strains caldimonas sp. and tepidimonas sp. isolated from a Malaysian hot springs - Mohd ghazali, Sharul Azim; Tengku Abdul Hamid, Tengku Haziyamin (Penerbit UKM, 2015)
Microbial lipolytic enzymes have attracted considerable attention owing to their biotechnological potential. In this study, thermophilic bacteria producing lipase were isolated from Bentong and Sungai Lembing hot springs, in Pahang, Malaysia. Out of 25 colonies isolated, 14 samples showed to produce clear zones surrounding the growth on tributyrin and trioelin agar plates. All 14 isolates showed Gram-negative bacteria with short rod morphology. PCR amplification of 16S ribosomal DNA gene showed that these isolates were clustered with subclass β-proteobacteria consisting of thermophilic bacteria that produce lipase. Phylogenetic analysis was carried out with the highly similar species and four isolates (SglA1, BtnC1, BtnC2 and BtnC3) are related to genus Caldimonas and 10 isolates (SglB1, SglB2, SglB3, SglB4, BtnB1, BtnB2 BtnD1, BtnD2, BtnD3 and BtnD4) belonged to genus Tepidimonas. These results indicated that novel lipase-producing thermophilic β-proteobacteria could be isolated from these hot springs